Odpowiedź:
a) -3x = 2x - 10
-3x-2x=-10
-5x=-10 /:(-5)
x= 2
b) 2x - 2 = 7 - x
2x + x = 7 + 2
3x = 9 /:3
x= 3
c) 10 = 4 - 2x
2x = 4 - 10
2x = -6 /:2
x = -3
d) 0,5y= 7 - 3y
0,5y + 3y = 7
3,5y= 7 /:3,5
y= 2
e) -(2x - 1) = 4
-x = 4
x = -4
f) 2(x+1)= x
2x + 2 = x
2x - x = -2
x= -2
g) 9(x + 8) = 9x + 8
9x + 72 = 9x + 8
9x - 9x = 8 - 72
x = -64
(tego nie jestem pewna ^)
h) 2t - (3t + 1) = 6
2t - 4t = 6
-2t = 6 /:(-2)
t = -3
i) -(4 + x) = 2(3-x)
-4 + x = 6 - 2x
x + 2x = 6 + 4
3x = 10 /:3
x = [tex]\frac{10}{3}[/tex]
(x = 3 [tex]\frac{1}{3}[/tex])
j) 4(a - 1) = 6 (1 + a)
4a - 4 = 6 + 6a
4a - 6a = 6 + 4
-2a=10 /:(-2)
a = - 5
k) 3(y + 6) - y = 2(y + 9)
3y + 18 -y = 2y + 18
3y - y - 2y = 18 - 18
0=0
l) (x-7) -2 (3x + 5) = 3
- 6x -6x - 10 = 3
-6x-6x=3+10
-12x=13 /:(-12)
x = [tex]-\frac{13}{12}[/tex]
(x= - 1 [tex]\frac{1}{12}[/tex])
Wyjaśnienie:
Nie jestem pewna niektórych, ale 70% z nich jest na pewno dobrze